PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS FLIPBOOK UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI PEMANGKASAN RAMBUT TEKNIK UNIFORM LAYER DI SMK NEGERI 1 LAMONGAN - Cicik Nilawati; Dewi Lutfiati; Octaverina Kecvara Pritasari; Mutimmatul Faidah (Program Studi Pendidikan Tata Rias, 2025)
Abstract Effective educational tools are crucial in enhancing students' comprehension, abilities, and academic results. One creative option is interactive flipbooks, which deliver content in a more visual and engaging manner. The objective of this research is to evaluate the viability of flipbook media, assess its impact on educational outcomes, and explore student feedback regarding its application. The study adopted a quantitative methodology, involving 26 students from grade XII as participants. It followed an eight-step process, which included (1) identifying potential issues, (2) gathering data, (3) creating a design, (4) validating it, (5) revising the design, (6) conducting trials, (7) refining the product, and (8) testing the implementation. The research framework utilized a One-Group Pretest-Posttest model to assess shifts in learning results. Data collection methods, including observations, learning outcome evaluations, and surveys, were analyzed through averages and t-tests. Findings indicated that the flipbook media achieved a high feasibility rating, with a score of 4.41, categorized as